2016
DOI: 10.1038/srep36399
|View full text |Cite
|
Sign up to set email alerts
|

Bone augmentation after ectopic implantation of a cell-free collagen-hydroxyapatite scaffold in the mouse

Abstract: The bone grafting is the classical way to treat large bone defects. Among the available techniques, autologous bone grafting is still the most used but, however, it can cause complications such as infection and donor site morbidity. Alternative and innovative methods rely on the development of biomaterials mimicking the structure and properties of natural bone. In this study, we characterized a cell-free scaffold, which was subcutaneously implanted in mice and then analyzed both in vivo and ex vivo after 1, 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 39 publications
(58 reference statements)
5
44
0
Order By: Relevance
“…Calabrese et al in their studies tested a composite bi-layer type-1 collagen-HA/Mg scaffold for osteochondral regeneration, both in vitro and in vivo. They showed that the combination of this scaffold with mesenchymal stem cells (MSC) derived from adipose tissue (hAD-SCs) in the presence of specific differentiation conditions induce osteochondro differentiation both in vitro and in vivo [19][20][21][22][23].…”
Section: Ceramicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calabrese et al in their studies tested a composite bi-layer type-1 collagen-HA/Mg scaffold for osteochondral regeneration, both in vitro and in vivo. They showed that the combination of this scaffold with mesenchymal stem cells (MSC) derived from adipose tissue (hAD-SCs) in the presence of specific differentiation conditions induce osteochondro differentiation both in vitro and in vivo [19][20][21][22][23].…”
Section: Ceramicsmentioning
confidence: 99%
“…Also, our group tested in vitro and in vivo potential of collagen type-1/Ha-Mg combination to promote bone injury healing. We demonstrated that although biomimetic scaffolds are "per sè" able to promote tissue regeneration thanks to their high osteoinductivity, their combination with progenitor cells and growth factors would be more efficient [19][20][21]. Generally, osteogenic cells such as adult stem cells (ASC) isolated from adult tissues like bone marrow, adipose tissue, or muscle are good candidate to be transplanted in skeletal lesion together with an appropriate scaffold.…”
Section: Biomaterials For Bone Tissue Engineering: Current Applicatiomentioning
confidence: 99%
“…The noncollagenous proteins form only 10% of the bone mass. [13] The glycoproteins are represented by alkaline phosphatase, bone sialoprotein, osteopontin and osteocalcin (which modulate the mineralization process) and osteonectin (determines the diameter of collagen fibrils) [14,15]. The proteoglycans are up to 10% of the non-collagenous proteins and offer resistance to compressive forces; they also have the capacity to bond to growth factors that can be stored in bone extracellular matrix for future use [7].…”
mentioning
confidence: 99%
“…A similar approach was carried out in the last decade to reproduce the spongy bone part (Sprio, Panseri, Cunha, & Tampieri, 2012;Tampieri, Sprio, Sandri, & Valentini, 2011). Hybrid porous scaffolds were obtained by a biomineralization process, that is, heterogeneous nucleation of hydroxyapatite on collagen matrix, that resulted in high regenerative ability in several preclinical and clinical studies (Calabrese et al, 2016;Kon et al, 2010;Minardi et al, 2015;Torres-Raya et al, 2008). In this light the scaffold of this study was designed as a bi-layer device associating: (a) BioSiC, developed as a mechanically-resistant porous shell, and presenting a hierarchic structure translated from the original wood template with (b) a soft, highly bioactive scaffold obtained by biomineralization, presenting bone-mimicking phase and atomic composition (i.e., the inorganic phase was Mg-and CO 3 -co-substituted hydroxyapatite [Mg-CHA] (Sprio et al, 2012;Tampieri et al, 2003)), and character- growth factors in osteoconductive matrix) is well accepted, and promising results have been already shown (Filardo et al, 2014).…”
Section: It Was Previously Tested On a Load-bearing Bone Defect In Shmentioning
confidence: 99%